2003
DOI: 10.1300/j005v25n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Youth Gangs in Honolulu

Abstract: Traditional theories of the connection between immigrant youth and gangs have not been sufficient in explaining why some are not in gangs. Therefore, this study examines Vietnamese youth gangs in Honolulu and the factors contributing to Vietnamese delinquency and youth gang participation. Twenty-six interviews were conducted with agency, school, police, Vietnamese adults, and Vietnamese youth. Results suggest that though the content of the delinquency model is different for immigrant and nonimmigrant youth, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Similarly, research has suggested that Koreans are generally less acculturated to the U.S., as reflected in their generally higher level of ethnic identity, practicing of Korean customs, speaking Korean, and being involved in Korean organizations (Min, 1995). And lastly, given that Vietnamese Americans represent among the most recent immigrant groups in the U.S., their lower level of acculturation is not surprising (Thai, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has suggested that Koreans are generally less acculturated to the U.S., as reflected in their generally higher level of ethnic identity, practicing of Korean customs, speaking Korean, and being involved in Korean organizations (Min, 1995). And lastly, given that Vietnamese Americans represent among the most recent immigrant groups in the U.S., their lower level of acculturation is not surprising (Thai, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…The few studies that do exist found that among Chinese, Korean, and Japanese American youth, there is a direct and positive relationship between delinquent peer association and delinquent behavior (Kim & Goto, 2000). Thai (2003) also found that Vietnamese adolescents who associate with delinquent peers and who have problems in the home, school, or neighborhood are apt to become delinquents or to join gangs. In contrast, Vietnamese youth who do not associate with delinquent peers, but who have the same problems, are less likely to exhibit delinquent behavior, or to become gang members.…”
Section: Peer and Delinquencymentioning
confidence: 92%